NOMA and Millimeter-Wave-Assisted SWIPT for Full-Duplex Cooperative D2D Communications - Rahul Bajpai; Sukriti Mishra; Naveen Gupta (IEEE Access)
This paper presents a novel approach by combining simultaneous wireless information and power transfer (SWIPT) with non-orthogonal multiple access (NOMA) and millimeter-wave (mmWave)-assisted full-duplex (FD) device-to-device (D2D) communications, a configuration not extensively explored in existing literature. Specifically, the proposed system utilizes a SWIPT-enabled D2D user that harvests energy from the base station, thereby facilitating cellular downlink transmission. In addition, directional antennas at both transmitting and receiving nodes are employed to effectively counteract frequency-dependent path loss, significantly enhancing system performance in mmWave frequencies. The novelty of this work lies in its comprehensive analysis, where analytical expressions of outage probabilities are derived, and these are validated through Monte Carlo simulations. Further, the impact of key system parameters, including signal-to-noise ratio, energy harvesting coefficient, and power allocation, on outage performance is thoroughly examined.